Total Synthesis of Lepadiformine Alkaloids using N-Boc α-Amino Nitriles as Trianion Synthonsa - Perry, Matthew A. (2012)
Lepadiformine A, B and C were synthesized in enantiomerically pure form using a reductive cyclization strategy. N-Boc α-amino nitriles were deprotonated and alkylated with enantiomerically pure dibromides to afford the first ring. The products were manipulated to introduce phosphate leaving-groups, and subsequent reductive lithiation followed by intramolecular alkylation formed the second ring with high stereoselectivity. The third ring was formed by intramolecular displacement of a mesylate by the deprotected amine. Lepadiformine A and B contain a hydroxymethyl group adjacent to the amine. This appendage was introduced in a sequence using a Polonovski-Potier reaction as the key step. The synthetic strategy is stereoselective and convergent, and demonstrates the utility of N-Boc α-amino nitriles as linchpins for alkaloid synthesis.